Wetenskaplike Voorraadbestuur - J. C. Engelbrecht (South African Journal of Business Management, 1970)
It is generally accepted that inventories cost money, but often only the cost of capital tied up in stock is considered, and management attempts to keep inventory levels as low as possible.